Impact of Pilates on the Intensity of Pain in the Spine of Women of the First Mature age - Vitalii Kashuba; Yuliia Tomilina; Nataliia Byshevets; Inna Khrypko; Olha Stepanenko; Igor Grygus; Olga Smoleńska; Svetlana Savliuk (OVS LLC, 2020)
The purpose of the study is to determine the dynamics of pain intensity in different parts of the spine in women of the first mature age under the influence of pilates. Materials and methods. 64 women took part in research. The women were divided into two groups, each of which included 32 people. The study was carried out at the Sokol sports club and the Olimp fitness club in Kiev. We used the questionnaire "Visual analogue scale of pain".  Results. We measured the level of pain in the cervical, thoracic and lumbar spine of women of the first mature age. It was found that only 4.69 % of women do not have pain. It was found that women of the first mature age the most often feel painin the cervical region. The women of the control group were engaged in a typical Pilates program. The women of the experimental group were engaged in the author's program, a feature of which was the use of large equipment during classes. In addition, women who could not attend classes were offered the Pilates computer program. For the experiment, no statistically significant difference between the level of pain in different parts of the spine of women was established. After the experiment, a statistically significant decrease in the level of pain in the lumbar section of women in the experimental group was recorded compared with women in the control group.  Conclusions. The results indicate the effectiveness of large equipment to reduce the level of pain in the back of a woman.